Directing a Short Movie Rawuh (Aplication Central Character One Pont of View On Jumarno Character) - Agung Kurniawan; Fajar Aji; Muhammad Zamroni (Program Studi Film dan Televisi Universitas Jember, 2019)
Indonesia is one of the countries which discloses migrant workers as an insolubility issue where several laborers are choosing illegality way of being migrant apprentices. Most reasons are caused by lack of understanding placement and protection procedures, limited information to access international job vacancy, inequitable registration through the unauthorized bureau, and lack of government involvement. As a result, many workers were unpaid and faced violent. In addition, human trafficking is also encountered migrant workers. Consequently, they are deported to their origins. Based on those backgrounds, the author would convey these issue into fiction movie through parents viewpoint as the person who left by migrant workers (Rabiger and Cheerrier, 2013:115). cinematic point of view, central character one point of view will be used to build narrative elements and cinematic elements in the film Rawuh, from the pre-production, production and post-production stages. RAWUH could depict Indonesian civilization, especially migrant worker issue that happened in Jember. The creator believes that directing with central character one viewpoint technique needs to develop in the future, especially on the storytelling scheme, mise en scene, cinematography, exploration of sound design, and editing.